Agricultural risks, the COVID-19 pandemic, and farm household welfare and diversification strategies in Africa - Abdul Malik Iddrisu; Alhassan Abdul-Wakeel Karakara; Evans Osabuohien (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
Agricultural activities in many African countries are bedevilled by a range of risk factors. Using micro-level household datasets from a range of countries in Africa, we examine the drivers of agricultural risks, while exploring the role of context as well as the impact of the COVID-19 pandemic on household welfare, with a focus on farm households relative to their non-farm counterparts. We demonstrate that the probability of experiencing risks related to agriculture is significantly influenced by a range of individual- and farm-level/contextual factors, with these effects showing considerable variations across contexts and countries in Africa. We also find that farm households witnessed important reductions in their incomes during the COVID-19 period in Uganda. The study contributes to the design of evidence-based approaches to reducing farmers' vulnerabilities to agricultural risks and pandemic-related shocks.
Keywords: I31; O55; Q15; R14; 330; agricultural risk; COVID-19 pandemic; farm households; welfare; Africa